Christianity, Globalization, and Protective Homophobia Democratic Contestation of Sexuality in Sub-Saharan Africa - Kaoma, Kapya (Springer International Publishing, 2018)
This book examines how socio-political assumptions inform and shape the contestation of sexuality on the African continent. Across Africa, the idea that homosexuality is un-African, un-Christian, un-natural, and un-cultural is now well established. This book analyzes politically- and religiously-inspired protective homophobia within the context of Africa's socioeconomic and political place in the global community. The author builds upon on-the-ground research and his groundbreaking previous studies on the cultural politics of globalization in Africa to present a wide, complex, and interdisciplinary understanding of Africa's sexual politics.